Zbirka rešenih izpitnih nalog iz Stabilnosti konstrukcij - Imamović, Denis; Peruš, Iztok (University of Maribor Press, 2020)
Stability of Structures - Collection of Completed Examinations. The work entitled Stability of structures - Collection of completed examinations is primarily intended for students of civil engineering as a study material to prepare for the exam of the subject Stability of Structures at the second level of the Master’s study program at the Faculty of Civil Engineering, Transportation Engineering and Architecture in Maribor. The authors hope that the work will find its way to students and that they will use it together with the notes from the lectures in the independent study of the subject, and not just for scrolling when sitting tests and exams. Some tasks are presented with several different methods and approaches to solve the problem, allowing a broader view of solving the problem of structural stability. Additionally, wherever possible, the results were verified with software SAP2000 using the finite element method. It should be emphasized that the work does not cover the entire content of the lecture material in the subject Stability of Structures and cannot be a substitute for the basic study material. However, it certainly serves for better understanding and consolidation the knowledge gained from the lectures, and as such it is a welcome help for exam preparation.